1994
DOI: 10.1093/clinchem/40.7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Comparable detection of acute myocardial infarction by creatine kinase MB isoenzyme and cardiac troponin I

Abstract: Although measurement of cardiac troponin I (cTnI) is, in some situations, more specific for detection of cardiac injury than is measurement of the MB isoenzyme of creatine kinase (MBCK), its sensitivity and specificity relative to MBCK for detection of myocardial infarction has not been established. Accordingly, we studied prospectively 199 consecutive patients admitted to the coronary care unit. Values of MBCK and cTnI mass were determined in all samples. Of the 188 patients admitted with a suspicion of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(84 citation statements)
references
References 20 publications
0
80
0
4
Order By: Relevance
“…In human cardiomyocytes, approximately 6-8% of total cellular cardiac troponin is cytosolically dissolved and thus unbound in cytoplasm. 21 Early after myocardial cell injury, affecting cell membrane permeability, parts of this free pool are liberated into the blood stream, but the majority of cTnI is retained intracellularly because of structural linkage to the contractile apparatus. Thus, release of cTnI may occur monophasically, with only minor increase after reversible myocyte injury, or bi-or polyphasically with more severe injury of the myocardium affecting the structurally bound portion of cTnI.…”
Section: Discussionmentioning
confidence: 99%
“…In human cardiomyocytes, approximately 6-8% of total cellular cardiac troponin is cytosolically dissolved and thus unbound in cytoplasm. 21 Early after myocardial cell injury, affecting cell membrane permeability, parts of this free pool are liberated into the blood stream, but the majority of cTnI is retained intracellularly because of structural linkage to the contractile apparatus. Thus, release of cTnI may occur monophasically, with only minor increase after reversible myocyte injury, or bi-or polyphasically with more severe injury of the myocardium affecting the structurally bound portion of cTnI.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative ischaemia seems to correlate with adverse outcome, and prolonged subendocardial ischaemia rather than acute coronary artery occlusion precedes cardiac complications [1,6]. Cardiac troponins (TNs) -troponin T (TNT) and troponin I (TNI) -have been established as a sensitive marker for detection of major and minor myocardial cell injury, avoiding the high incidence of false-positive results by the use of creatine kinase (CK)-MB [7][8][9][10][11][12]. Metzler et al [13] found that in cardiac risk patients undergoing non-cardiac surgery high postoperative levels of TNT and TNI were correlated with post-operative cardiac complications, whereas patients with no or only slightly increased concentrations of both troponins had a good outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of biomarkers have been used to assess cardiac myocyte damage, including aspartate dehydrogenase, creatinine kinase, lactate dehydrogenase, myoglobin and cardiac troponin (cTn) (Adams et al 1993, Spratt et al 2005, Jaffe et al 2006. Cardiac troponin I (cTnI) is exclusively found in the myocardium and is a sensitive and specific marker of myocyte damage (Adams et al 1993(Adams et al , 1994. Serum cTnI concentrations have been measured in many species to non-invasively assess myocardial damage (Apple et al 2008, Mikaelian et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The median time between the pre-and post-diagnosis samples in this study was 4 weeks, which provided sufficient time to examine the relationship between changes in HCT and serum cTnI concentrations. After an acute cardiac injury the cytosolic pool, which is about 2 to 4% of total cTnI (Adams et al 1994), is released, causing an early peak in serum cTnI concentrations. The peak in cTnI concentrations in canine models of acute myocardial infarction has been reported to occur 10 to 16 hours post infarction (Cummins & Cummins 1987).…”
Section: Discussionmentioning
confidence: 99%